Persepsi Guru tentang Proses Supervisi oleh Kepala Sekolah di SMKN 2 Bukittinggi - Nindi Elissa; Sulastri Sulastri; Ermita Ermita; Lusi Susanti (Universitas Negeri Padang, 2021)
This research is based on the result of the author’s observation of the supervision process which in its implementation is still not running effectively in SMK Negeri 2 Bukittinggi. The purpose of this research is to obtain data on the teacher’s view on supervision activities seen in the following indicators: supervision planning, supervision implementation, supervision evaluation and follow-up supervision results. This research uses descriptive research using quantitative methods. The population in this study was all civing servant teachers in SMK Negeri 2 Bukittinggi which amounted to 80 people, and the amount of samples taken from respondents was 74 people. The sample withdrawal in this study uses proportional stratified random sampling technique. The data obtained has been tested for validity and reliability. The average formulation is used in processing data in this study. The data showed the teacher’s view of supervision activities: (1) planning scored with an average of 4,28 good categories; (2) implementation of getting a score with an average of 4,35 good average (3) evaluation gets a score with an average of 4,34 good category; (4) follow-up result get a score with a good category average of 4,33. The results obtained in this study were about the teacher’s view of the process of obtaining a score with an average of 4,33 good categories. The data obtained has been tested for validity and reliability. The average formulation is used in processing data in this study.